Synchronization during an internally directed cognitive state in healthy aging and mild cognitive impairment: a MEG study - López, María Eugenia; Garcés, Pilar; Cuesta, Pablo; Castellanos, Nazareth; Aurtenetxe, Sara; Bajo, Ricardo; Marcos, Alberto; Montenegro, Mercedes; Yubero, Raquel; del pozo, Francisco; Sancho, Miguel; Maestú, Fernando (AGE, 2017)
Mild cognitive impairment (MCI) is a stage between healthy aging and dementia. It is known that in this condition the connectivity patterns are altered in the resting state and during cognitive tasks, where an extra effort seems to be necessary to overcome cognitive decline. We aimed to determine the functional connectivity pattern required to deal with an internally directed cognitive state (IDICS) in healthy aging and MCI. This task differs from the most commonly employed ones in neurophysiology, since inhibition from external stimuli is needed, allowing the study of this control mechanism. To this end, magnetoencephalographic (MEG) signals were acquired from 32 healthy individuals and 38 MCI patients, both in resting state and while performing a subtraction task of two levels of difficulty. Functional connectivity was assessed with phase locking value (PLV) in five frequency bands. Compared to controls, MCIs showed higher PLV values in delta, theta, and gamma bands and an opposite pattern in alpha, beta, and gamma bands in resting state. These changes were associated with poorer neuropsychological performance. During the task, this group exhibited a hypersynchronization in delta, theta, beta, and gamma bands, which was also related to a lower cognitive performance, suggesting an abnormal functioning in this group. Contrary to controls, MCIs presented a lack of synchronization in the alpha band which may denote an inhibition deficit. Additionally, the magnitude of connectivity changes rose with the task difficulty in controls but not in MCIs, in line with the compensation-related utilization of neural circuits hypothesis (CRUNCH) model.
Keywords: mild cognitive impairment; Internally Directed Cognitive State (IDICS); functional connectivity; MEG; CRUNCH; JCR; Scopus